Bilateral undescended testes with intraabdominal non seminomatous germ cell tumor – a rare clinical challenge - Aher, Kalyani D.; Gadahire, Minakshi (International Journal of Research in Medical Sciences, 2026)
Cryptorchidism is the most common congenital anomaly of the male genitalia, with nearly 72-77% of undescended testes located in the inguinal canal. Among malignancies arising in undescended testes, seminoma is the most frequent type, accounting for approximately 50-60% of cases. Tumors arising from intra-abdominal testes may grow to considerable sizes before detection, and delayed diagnosis often results in advanced-stage disease at presentation. We report a case of bilateral cryptorchidism in a young male who presented with vague lower abdominal pain, without any prior history of abdominal swelling or distension. The patient had noticed an empty scrotum since around 10 years of age but did not seek medical evaluation due to social stigma. Eventually, at the age of 21 years, he developed a large intra-abdominal non-seminomatous germ cell tumor arising from an undescended testis. The patient subsequently underwent an exploratory laparotomy with right radical orchidectomy and left orchidectomy, followed by advice to undergo adjuvant chemotherapy and regular follow-up.